2020
DOI: 10.1063/1.5139269
|View full text |Cite
|
Sign up to set email alerts
|

Observing relaxation in device quality InGaN templates by TEM techniques

Abstract: Device quality InGaN templates are synthesized using the semibulk (SB) approach. The approach maintains the film's 2D growth and avoids the formation of indium-metal inclusions. The strain relaxation processes of the grown InxGa1−xN templates are accompanied by variations in the indium content (x) and lattice parameters (a and c) across the InGaN template's thickness as the residual strain is continuously decreasing. This strain and lattice parameters' variation creates difficulties in applying standard x-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…for the growth of thick InGaN layer on GaN template [25,26]. Then, the active zone was implemented with 5x In y Ga 1-y N/In x Ga 1-x N multiple quantum wells (MQWs) with average well and barrier widths of 2.3 nm and 6 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…for the growth of thick InGaN layer on GaN template [25,26]. Then, the active zone was implemented with 5x In y Ga 1-y N/In x Ga 1-x N multiple quantum wells (MQWs) with average well and barrier widths of 2.3 nm and 6 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…While many trials have been realized to get a relaxed InGaN buffer layer either from a GaN template (GaN buffer layer on sapphire substrate) or a sapphire substrate, no results with high crystalline quality have been demonstrated yet [19][20][21][22][23][24]. However, M. Abdelhamid et al have recently demonstrated the possibility to get an In 0.08 Ga 0.92 N buffer layer almost fully relaxed on a GaN template with a good material quality by using the semi-bulk technique [25,26]. The electrochemical porosification of the GaN layer beneath the InGaN buffer seems also promising [27].…”
Section: Introductionmentioning
confidence: 99%
“…This approach maintains smooth surfaces and is acceptable for further epitaxial growth. Semi-bulk structures are favorable for producing [68], Copyright (2020), with permission of AIP Publishing.…”
Section: Periodic Ingan Structuresmentioning
confidence: 99%
“…Eldred et al reported that the InGaN QWs grown on periodic InGaN structures had a large red-shift of 12−35 nm, implying the improvement of crystal quality due to the reduction of compressive strain. 21 more, theoretical studies of In incorporation and surface segregation processes have been carried out by Duff et al They found that the considerably reduced growth window due to compressive strain could be widened by growing on latticematched In 0.25 Ga 0.75 N underlying layers. 23 Most of these studies show that the relaxed underlying layers reduce the compressive strain and thus improve the performance of InGaN QWs.…”
Section: Introductionmentioning
confidence: 99%